Cover Feature: Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo (Chem. Eur. J. 31/2020). Issue 31 (8th May 2020) - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus
Abstract : Pseudo isocyanine chloride (PIC) is a dyestuff which forms J‐aggregates below a concentration‐dependent temperature threshold. Co‐solutes with excluded volume effects promote J‐aggregation by increasing the temperature threshold. The J‐aggregates exhibit a sharp fluorescence band enabling their detection in cells. Fluorescence imaging with HeLa cells exposed to dilute solutions of PIC monomers reveals a strong J‐aggregation, thus providing a model system to sense macromolecular crowding in vivo. More information can be found in the Full Paper by S. Ebbinghaus, K. Huber, et al. on page 7041 .